P182 Bowel wall thickness as seen on point-of-care intestinal ultrasound correlates with endoscopic severity in children with Inflammatory Bowel Disease: A North American diagnostic cross-sectional study. (27th May 2021) - Chavannes, M; Hart, L; Dillman, J R; Marachelian, A; Polk, D B
Abstract: Background: In pediatric patients with Inflammatory bowel disease (IBD), delay in diagnosis can lead to progression of disease and bowel damage. In North America, the current methods to visually assess disease activity are limited to ileocolonoscopies and MR enterography. Point-of-care intestinal ultrasound (IUS) is a non-invasive, cost-efficient tool for assessing intestinal inflammation. We aim to evaluate the correlation between IUS and endoscopic disease activity in children suspected to have IBD. Methods: In this cross-sectional study, we recruited consecutive patients newly diagnosed with IBD, presenting to the IBD outpatient clinic, or hospitalized in our pediatric center between August 2020 and February 2021. In addition to ileocolonoscopy, they underwent IUS performed by one gastroenterologist who was blinded to ileocolonoscopy results at the time of performing IUS. Bowel wall thickness (BWT) was measured systematically across different bowel segments (terminal ileum, ascending, transverse, descending, sigmoid colon, and rectum) and recorded twice in longitudinal view and twice in axial view. An average segmental BWT of more than 3 mm was considered inflamed. The inflammation seen on endoscopy was graded using segmental scores of the SES-CD for patients with Crohn's disease (CD) and the UCEIS for patients with ulcerative colitis (UC). Segments were classified as healed, mild, moderate, or severe disease activity. The association between the BWT and disease severity on endoscopy was assessed using the Kruskal-Wallis test. Numerical correlation between BWT and continuous values of the endoscopic scores was performed using Kendall's Tau-b. Results: Fifteen patients completed both IUS and ileocolonoscopy. A total of 74 bowel segments were assessed. There were 7 girls, median age of 15 years (IQR 12.5–15.5 years). 8 patients were diagnosed with CD, 5 with UC, and 2 had a normal endoscopy. Median PCDAI was 32.5 (IQR 30.0–40.0), and median PUCAI was 70 (IQR 70–75). The Kruskal-Wallis test showed that BWT was significantly associated with disease severity as measured by the SES-CD (chi-square = 14.3, p <0.001, df = 2) for patients with CD, and that the BWT was also significantly associated with disease severity as measured by the UCEIS (chi-squared=12.0, p<0.001, df=3). The numerical correlation between BWT and SES-CD for all segments was 0.43 (p<0.001, 95%CI 0.3–0.58), while the correlation with the UCEIS was 0.52 (p<0.001, 95%CI 0.4–0.66). Conclusion: In pediatric patients with IBD, we found that endoscopic disease severity correlates with the degree of BWT seen on IUS. These findings support the use of IUS as an evaluation tool of disease activity in North American pediatric clinical practice.